If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1l + -19l + -1 + -23 + -2 = 0 Reorder the terms: -1 + -23 + -2 + -1l + -19l = 0 Combine like terms: -1 + -23 = -24 -24 + -2 + -1l + -19l = 0 Combine like terms: -24 + -2 = -26 -26 + -1l + -19l = 0 Combine like terms: -1l + -19l = -20l -26 + -20l = 0 Solving -26 + -20l = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + -20l = 0 + 26 Combine like terms: -26 + 26 = 0 0 + -20l = 0 + 26 -20l = 0 + 26 Combine like terms: 0 + 26 = 26 -20l = 26 Divide each side by '-20'. l = -1.3 Simplifying l = -1.3
| -19l-l-23-2= | | 5y^2-16+11=0 | | -4(-6)+y=29 | | -91=9t+8 | | 7x^3-x^2-112x+16=0 | | x+(x*.15)=27.6 | | 5(8c-1)-12=38c+5 | | .50(10x-2)=4 | | 34-52(12n-34)+235=32+101(35n-1) | | x^3+2x=110 | | 26a+26b= | | 15s^2+32s-7=0 | | 146-3x=33x+18 | | 11-9x=175-37x | | 0.0625x^2-0.125x=1 | | x^2-2x+1=8 | | 18x-(2x-8)=40 | | 37-3x=6x+27 | | 68-4x=8x-20 | | 7-8x=127-29x | | -10=-5(t-8) | | 7-8x=127-39x | | z^2-15=0 | | 3(x+7m+5)= | | 3x-12=4x-12 | | 50(x)=-0.4x^2+80x-1600 | | -21=7y | | 5(x+2)-7(x-1)=1 | | c+5=3 | | (8z-2)(8-z)=0 | | x(7x+32)+33=0 | | 2m=m+6 |